251 Late-Breaking: Mucosal disaccharidase kinetics in the jejunum of steers with a divergent average daily gain. (7th December 2018) - Brake, D; Smith, W; Oliver, W; Freetly, H; Foote, A
Abstract: The objective of this study was to quantify the differences in activity of maltase and isomaltase within the jejunum between two groups of steers with average dry matter intake (DMI) and differing average daily gain (ADG). Feed intake and growth were measured in a cohort of 69 crossbred steers consuming a finishing diet containing 67.8% dry-rolled corn, 20% wet distillers grains with solubles, 8% alfalfa hay, and 4.2% vitamin/mineral supplement on a dry matter basis. The greatest (high) and least (low) ADG steers that were within the mean ± 0.55 SD for DMI were chosen for slaughter and jejunum mucosa collection (n = 8 for each group). Homogenates of jejunal mucosa were incubated with increasing amounts of maltose and isomaltose to determine the kinetics of the disaccharidases.Neither the Km (P = 0.15) or the Vmax expressed per gram of protein (P = 0.11) or tissue (P = 0.18) differed between groups of steers. Similarly, neither the Vmax for maltase expressed per gram of protein (P = 0.33) or tissue (P = 0.45), nor the Km (P = 0.43), for maltase differed between group. The protein concentration of the mucosa did not differ between the two groups (P = 0.45). Small intestinal weight between the two groups did not differ (P = 0.69). Plasma urea nitrogen, cholesterol, triglycerides, β-hydroxybutyrate, non-esterified fatty acids, and lactate did not differ between the groups (P > 0.05). There was a group x day interaction for plasma glucose (P > 0.01), indicating that glucose only differed between the groups on day 42. While previous studies have indicated that disaccharidase expression is associated with differences in ADG, data presented here indicate that differences in enzyme activity are minimal. USDA is an equal opportunity provider and employer.